Bridging the gap: enhancing clinical decision-making in undergraduate anaesthesiology training through branching scenario method - Ramly, Nur Fariza; Abdul Karim, Aidah (Fakulti Pendidikan, Pusat Pendidikan dan Kesejahteraan Komuniti, UKM, 2025)
This study aimed to evaluate the usability and effectiveness of Anaesthesiology Branching Clinical Scenario (ABCS) module in enhancing undergraduate medical students’ ability in clinical decision-making. The module incorporate interactive, scenario-based learning rooted in constructivist and andragogical principles. A convergent mixed method design was used, involving 30 Year 4 medical students from IIUM. Data collection methods included pre- and post-intervention tests to measure knowledge application, the USE questionnaire to assess usability, open-ended questionnaires and focus group interviews. The ABCS was designed using screen-based simulations and embedded clinical decision points relevant to perioperative care. Usability and learning outcomes were measured through descriptive and inferential statistics, and thematic analysis was applied to qualitative data. Results indicated a significant improvement in post-test scores (mean difference = 3.4, Z = -4.21, p < .001, r = .53), with all students achieving the learning outcome with minimum mark of 12/20. Usability scores from students and educators were high, particularly in ease of learning (mean = 4.9 ± 0.3 for students and 5.0 ± 0.0 for educators). Qualitative data highlighted enhanced engagement, improved decision-making, and relevance to curriculum objectives. The ABCS module offers a practical and cost-effective complement to traditional teaching methods, especially in settings where hands-on clinical exposure are limited. This research suggests that branching scenario tools can support competency-based medical education and improve knowledge translation into clinical practice. Future work should evaluate long-term retention and adaptive learning integration.